Bimbingan Keagamaan untuk Menurunkan Kenakalan Peserta Didik di sekolah - Abil Fida Muhammad Qois Al Hadi (Universitas Muhammadiyah Makassar, 2023)
The background to the problem of this research is how religious guidance contributes to reducing juvenile delinquency in schools. The aim of this writing is to provide an understanding of how religious guidance can deal with juvenile delinquency in the educational environment. This research uses a literature review. The approach used is hermeneutic-philosophical. This study is information that researchers seek by searching for literature according to the problems presented. Religious guidance helps teenagers solve their problems and create peace in their lives through religious guidance provided by mentors during the guidance process. Therefore, religious guidance can be said to play an important role in overcoming the problem of juvenile delinquency and can also make teenagers' lives more successful both in this life and in the afterlife.